Mass drug administration of azithromycin for trachoma reduces the prevalence of genital Chlamydia trachomatis infection in the Solomon Islands. (17th February 2016) - Marks, M; Bottomley, C; Tome, H; Pitakaka, R; Butcher, R; Sokana, O; Kako, H; Solomon, A W; Mabey, D C
Abstract : Objectives: Chlamydia trachomatis is the most common bacterial sexually transmitted infection and is frequently asymptomatic; ocular C. trachomatis strains cause trachoma. Mass drug administration (MDA) of azithromycin for trachoma might also reduce the prevalence of genital C. trachomatis . In a survey conducted in the Solomon Islands in 2014, prior to MDA, the prevalence of genital C. trachomatis was 20.3% (95% CI 15.9% to 25.4%). We conducted a survey to establish the impact of MDA with azithromycin on genital C. trachomatis . Methods: Women attending three community outpatient clinics, predominantly for antenatal care, 10 months after MDA with azithromycin given for trachoma elimination, were enrolled in this survey. Self-taken high vaginal swabs were for C. trachomatis and Neisseria gonorrhoeae using the BD Probetec strand displacement assay. Results: 298 women were enrolled. C. trachomatis infection was diagnosed in 43 women (14.4%, 95% CI 10.6% to 18.9%) and N. gonorrhoeae in 9 (3%, 95% CI 1.4% to 5.7%). The age-adjusted OR for C. trachomatis infection was consistent with a significant decrease in the prevalence of C. trachomatis following MDA (OR 0.58, 95% CI 0.37 to 0.94, p=0.027). There was no change in the prevalence of N. gonorrhoeae between following MDA (OR 0.51, 95% CI 0.22 to 1.22, p=0.13). Conclusions: This study demonstrated a 40% reduction in the age-adjusted prevalence of genital C. trachomatis infection following azithromycin MDA for trachoma elimination.